BEKOL SAVANNA REHABILITATION BY CONTROLLING VACHELLIA NILOTICA WITH TRICLOPYIR AND DESIRED GRASSES REPLANTING - Tjitrosemito, Soekisman; Irianto, Ragil; Garsetiarsih, Garsetiarsih; Setyawati, Titiek; Subiyakto, Atok; Susmianto, Adi (BIODIVERS - BIOTROP Science Magazine, 2024)
Research works were carried out from 2012 – 2015 to investigate success of controlling broadleaved weed and trees of V.nilotica and planting desired grasses The tretments were combined 3 factors. Factor 1, was the way to apply triclopyr formulated as GARLON 670 EC to control trees of V.nilotica, (1). by brushing the solution of 1% GARLON 670 EC dissolved in diesel oil on the stump of V.nilotica after cutting using a chainsaw, and by (2). brushing at the base of intact standing tree of V. nilotica, from above the ground up to 30 cm height. Factor 2, was grasses (1). Dichanthium caricosum, and (2). Polytrias amaura planted ad 1 x 1 m2. Factor 3 was fertilizer, (1) planted grasses were fertilized with compost derived from goat feces at 100 gr/ single chunk planted, and (2) without fertilizer. The results indicated that grass grew better under the treatment of killing V.nilotica by cutting and brushing with 1% GARLON 670 EC dissolved in diesel oil, while fertilizing D.caricosum was much better to than of P.amaura.